INVESTIGATING THE IMPACT OF MIXED TENURE POLICY ON THE OWNER, DEVELOPER, SOCIAL RENTER AND SOCIETY IN THE UK. - Dhanuka, Suyash (2007)
This project is concerned with the impact on developers of planning regulations in the UK housing sector. Government expectations, reflected in planning regulations, that new developments will have a mix of tenants, including those who purchase conventional market priced properties and those who access 'social housing' are a cause for concern among developers. In particular, many companies are concerned that the required mix of social and non social tenants will make new developments less attractive to prospective purchasers and investors. If conventional housing developments are infact unattractive because of these regulations, then developers with substantial land holdings may need to consider alternatives such as service apartment or hotels. The task is to investigate by literature review and my primary analysis that is the result of the questionnaire is to whether the policy is beneficial to the society on the whole or not.